Transcriptomic Profiling of Tape-Strips From Moderate to Severe Atopic Dermatitis Patients Treated With Dupilumab. Issue 1 (October 2021) - Mikhaylov, Daniela; Del Duca, Ester; Olesen, Caroline Meyer; He, Helen; Wu, Jianni; Ungar, Benjamin; Estrada, Yeriel; Zhang, Ning; Chowdhury, Mashkura; Clausen, Maja-Lisa; Krueger, James G.; Pavel, Ana B.; et al.
Abstract : Background: Tape-strips are a minimally invasive approach to characterize skin biomarkers in atopic dermatitis (AD). However, they have not yet been used for tracking gene expression changes with systemic treatment. Objective: The aim of the study was to evaluate gene expression changes and therapeutic response biomarkers in AD patients before and after dupilumab (interleukin 4Rα antibody) treatment using tape-strips to obtain epidermal tissue for analysis. Methods: Lesional and nonlesional tape-stripped skin was sampled from 18 AD patients before and after dupilumab treatment and from 17 healthy subjects and analyzed by RNA-seq. Results: At baseline, we detected 6745 and 4859 differentially expressed genes between lesional and nonlesional skin versus normal, respectively, whereas 841 and 977 genes were differentially expressed after treatment, respectively (fold change >1.5 and false discovery rate <0.05). Tape-strips captured significant modulation with dupilumab in key AD immune (eg, C-C motif chemokine ligand 13 [CCL13], CCL17, CCL18) and barrier (eg, periplakin, FA2H) biomarkers. Changes in biomarkers (CCL20, interleukin 34, FABP7) were also significantly correlated with clinical disease improvements (Eczema Area and Severity Index; R > 0.5 or R < −0.4, P < 0.05). Conclusions: This real-life study represents the first comprehensive RNA-seq molecular profiling of tape-strips from moderate to severe AD patients after dupilumab therapy. Analysis of tape strip specimens detected significant gene expression changes in key AD biomarkers with dupilumab treatment, suggesting that this approach may be useful to monitor therapeutic responses in inflammatory skin diseases. Abstract : Supplemental digital content is available in the text.